Pengaruh Strategi Marketing Personal Selling Terhadap Produktivitas Kinerja Karyawan BPR Syariah Dinar Ashri KC. Terara - Yunita Laela Habibah; Marjan Marjan; Susanti Susanti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of personal sales marketing strategies on employee performance productivity at BPR Syariah Dinar Ashri Terara Branch Office. In an era of increasingly fierce banking industry competition, financial institutions are required to optimize marketing strategies that not only focus on sales, but also build strong relationships between sales staff and consumers. Personal selling was chosen because of the emphasis on direct communication, persuasive approach, and the formation of trust, which are expected to increase work motivation and employee productivity. This study uses a quantitative approach with data collection techniques through observation, questionnaires, and documentation, then analyzed using validity tests, reliability tests, normality tests, and hypothesis tests through t-tests and coefficient of determination (R²) tests with the help of SPSS version 25. The results showed that personal sales did not have a significant effect on employee performance productivity, with a significance value of 0.342 and a t-count of 0.973 < t-table 1.717. These findings indicate that the implemented personal selling strategy has not been running optimally, so it is necessary to improve marketing staff training, mastery of sharia products, and strengthen communication techniques to be able to support the performance and competitiveness of BPRs in a sustainable manner.